"We aren't idlers": Using subjective group dynamics to promote prosocial driver behavior at long‐wait stops. Issue 11 (14th September 2018) - Player, Abigail; Abrams, Dominic; Van de Vyver, Julie; Meleady, Rose; Leite, Ana C.; Randsley de Moura, Georgina; Hopthrow, Timothy
Abstract: Idling engines are a substantial air pollutant which contribute to many health and environmental problems. In this field experiment ( N =  419) we use the subjective group dynamics framework to test ways of motivating car drivers to turn off idle engines at a long wait stop where the majority leave their engines idling. One of three normative messages (descriptive norm, in‐group prescriptive deviance, outgroup prescriptive deviance) was displayed when barriers were down at a busy railway level‐crossing. Compared to the baseline, normative messages increased the proportion of drivers that turned off their engines. Consistent with subjective group dynamics theory, the most effective approach was to highlight instances of in‐group prescriptive deviance (47% stopped idling, compared with 28% in the baseline). Implications for health and environmental outcomes and future research are discussed.